A comparison of the stellar, CO, and dust-continuum emission from three star-forming HUDF galaxies at z [approximately] 2 - Kaasinen, Melanie; Walter, Fabian; Novak, Mladen; Neeleman, Marcel; Smail, Ian; Boogaard, Leindert; Cunha, Elisabete da; Weiss, Axel; Liu, Daizhong; Decarli, Roberto; Popping, Gergö; Diaz-Santos, Tanio; et al. (The astrophysical journal, 2020)
We compare the extent of the dust, molecular gas, and stars in three star-forming galaxies, at z = 1.4, 1.6, and 2.7, selected from the Hubble Ultra Deep Field based on their bright carbon monoxide (CO) and dust-continuum emission as well as their large rest-frame optical sizes. The galaxies have high stellar masses, , and reside on, or slightly below, the main sequence of star-forming galaxies at their respective redshifts. We probe the dust and molecular gas using subarcsecond Atacama Large Millimeter/submillimeter Array observations of the 1.3 mm continuum and CO line emission, respectively, and probe the stellar distribution using Hubble Space Telescope observations at 1.6 μm. We find that for all three galaxies the CO emission appears ≳30% more compact than the stellar emission. For the z = 1.4 and 2.7 galaxies, the dust emission is also more compact, by ≳50%, than the stellar emission, whereas for the z = 1.6 galaxy, the dust and stellar emission have similar spatial extents. This similar spatial extent is consistent with observations of local disk galaxies. However, most high-redshift observations show more compact dust emission, likely because of the ubiquity of central starbursts at high redshift and the limited sensitivity of many of these observations. Using the CO emission line, we also investigate the kinematics of the cold interstellar medium in the galaxies, and find that all three have kinematics consistent with a rotation-dominated disk.